Utilising indigenous knowledge or crime against humanity?: a critical engagement with the debate generated by Alick Macheso's Use of Manhood to Treat Nhova (Sunken Fontanelle) - Tembo, Charles; Maganga, Allan; Dewah, Peterson (Unisa Press, 2022)
This article presents various points of view regarding the treatment of sunken fontanelle by various communities as ignited by the controversial practice of kutara (a practice that involves the father of a child sliding his penis from the lower part of the left and right cheeks to the top of the head, as well as from the lower part of the face to the top of the head, and from the lower back part of the head to the top). The story of Alick Macheso’s use of his manhood to treat nhova (sunken fontanelle) opened a Pandora’s box. The story not only attracted the attention of critics from diverse cultural and ethical backgrounds, but revealed multi - ethnic positions. That is, reactions were steeped in a multiplicity of intellectual, religious and even cultural grounding. Reactions ranged from accusations of backwardness and absurdity, through to medical and Christian orientations toward the treatment of nhova . The overarching idea is that there is a general tendency to dismiss the age - old practice of kutara, coupled with an uncritical celebration of certain positions. The debate that ensued following publication of the story seemed to revolve around ethical considerations. The school of thought that dismisses kutara with disdain regards it as unethical and unimaginable in the present - day world — it is redolent with insinuations of absurdity on the part of those that live and celebrate it. We contend that the raging debate that followed the publication of the story can best be conceptualised within the context of African ethics. We note that kutara has relevance to the spirituality, ethical values, privacy, and protection of children’s rights, among other ethical issues. It is hoped that the article will stir further debate and encourage more research among information practitioners, scholars and researchers into the ethical issues surrounding the treatment of sunken fontanelle in various African communities. It argues for an Afrocentric conceptualisation of phenomena in order to contribute to debates on the renaissance of African cultures, and stresses that it is imperative to harness the life - furthering age - old traditions in African ontological existence.